Use OF NBI for the assessment of clinical signs of rhino-pharyngo-laryngeal reflux in pediatric age: Preliminary results. (January 2020) - Galli, J.; Meucci, D.; Salonna, G.; Anzivino, R.; Giorgio, V.; Trozzi, M.; Settimi, S.; Tropiano, M.L.; Paludetti, G.; Bottero, S.
Abstract: Objectives: Laryngopharyngeal reflux (LPR) is a complex problem in pediatric population: diagnosis and clinical presentation are still controversial. Classic white light endoscopy shows some pathognomonic signs of LPR in children, such as thickening of pharyngo-laryngeal mucus, the cobblestoning aspect of pharyngeal mucosa, arytenoid edema/hyperemia, nodular thickening/true vocal cord edema, hypertrophy of the posterior commissure, subglottic edema. The NBI (Narrow Band Imaging) technology, generally used in oncology, allows to study neoangiogenesis and hypervascularization of the mucosa, common aspects in both chronic inflammation and neoplastic transformation. The aim of our study was to evaluate the added value of this technology in identifying the main laryngopharyngeal reflux sign in a pediatric population. Methods: We evaluated at the Otolaryngology Unit of the "Fondazione Policlinico A. Gemelli" hospital and the Airway Surgery Unit of the "Bambino Gesù" Children's Hospital 35 patients aged from 2 months to 16 years divided into two groups in the period between November 2017 and May 2018. Group A included patients with clinical suspicion of LPR after gastroenterologist evaluation and Group B included patients who underwent an endoscopic evaluation for the assessment of recurrent respiratory symptoms such as stridor, recurrent croup, wheezing and persistent cough. We performed an endoscopic evaluation by white light and NBI for each patient, comparing the results of both methods to evaluate signs of pharyngo-laryngeal reflux and to calculate the value of reflux finding score (RFS). Results: The analysis of the data showed: for Group A an average value of RFS with white light of 11, 84 (range 8–17, standard deviation 2, 52 ± 0, 57) and with NBI of 13, 63 (range 10–17, standard deviation 2, 13 ± 0, 49); for Group B the analysis of the data showed an average value of RFS with white light of 10, 06 (range 8–14, standard deviation 2, 32 ± 0, 58) and with NBI of 12, 50 (range 9–18, standard deviation 2, 63 ± 0, 65). The comparison between the two methods resulted significant. Furthermore evaluation by NBI allowed to highlight other signs of pharyngo-laryngeal reflux, characteristic of pediatric age and not included in RFS, in particular cobblestone aspect of the hypopharingeal mucosa, phlogosis of the tonsillar crypts and adenoid surface, hyperemia and hypervascularization of subglottic and tracheal mucosa. Conclusion: Although still preliminary our results represent an interesting starting point for further studies, because they underline the potentiality of NBI endoscopy in LPR evaluation and how this technology could improve the identification of reflux signs.